Leukemia and Risk of Venous Thromboembolism: A Meta-analysis and Systematic Review of 144 Studies Comprising 162,126 Patients - Ying-Ying Wu (Nature Portfolio, 2017)
Abstract Venous thromboembolism (VTE) has significant clinical implications in leukemia patients. However, the actual frequency of this complication remains unknown. We performed a systematic review and meta-analysis to better estimate the frequency of this complication and to assess the risk factors that contribute to its occurrence. We searched several databases, including PubMed, Embase, and Web of Science, and assessed study quality using the Newcastle–Ottawa scale. The pooled frequency of VTE in leukemia patients was calculated. A total of 144 studies met the eligibility criteria. The incidence rate (IR) of VTE from 72 prospective studies comprising 9,061 patients was 5% (95%CI: 4–6%). The incidence rate (IR) of VTE in ALL, CLL, total-AML, and CML population was 5% (95%CI: 4–6%), 3% (95%CI: 2–5%), 6% (95%CI: 4–8%) and 13% (95%CI: 1–36%). The incidence of VTE was markedly decreased among ALL patients who received anticoagulation treatment (IR: 1%, 95%CI: 0–6%) or concentrates therapy (IR: 3%, 95%CI: 0–9%). The overall incidence of VTE in the leukemia population was high, particularly in transplant recipients, who had the highest risk (IR: 8%, 95% CI: 4–13%). Prophylactic approaches could significantly decrease the occurrence of VTE events.